Tobacco‐specific nitrosamines – Determination of N‐nitrosoanabasine, N‐nitrosoanatabine, N‐nitrosonornicotine and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanol in urine by LC‐MS/MS [Biomonitoring methods, 2019]. Issue 4 (13th November 2019) - Scherer, G.; Gilch, G.; Köhler, D.; Völkel, W.; Göen, T.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area developed and validated the presented biomonitoring method. This analytical method permits the determination of tobacco‐specific nitrosamines (TSNA) in urine using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). The parameters in question are N ‐nitrosoanabasine (NAB), N ‐nitrosoanatabine (NAT), N ‐nitrosonornicotine (NNN) and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanol (NNAL). NNAL is a metabolite of 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK). Due to its sensitivity, this method is suitable for the detection of the aforementioned analytes in the urine of smokers. NNAL can also be quantified in the urine of passive smokers. The analytes NAB, NAT, NNN and NNAL are present in urine in both free and glucuronidated forms. For the determination of the total TSNA level in urine, the glucuronides are cleaved by enzymatic hydrolysis and then the analytes are isolated and concentrated using solid phase extraction (SPE). Two sorbent materials are used for sample preparation via SPE, first a material based on molecularly imprinted polymers and then a mixed‐mode cation exchange polymer. Analysis is performed by LC‐MS/MS. Deuterated internal standards are used for calibration. Calibration standards are prepared in pooled urine obtained from non‐smokers and are processed in the same way as the samples to be analysed.